Exfoliating Whales–Sandy Bottom Contact Behaviour of Humpback Whales - Jan-Olaf Meynecke; Johan Gustafon; David E. Cade (Journal of Marine Science and Engineering, 2023)
Cetaceans are known for their intelligence and display of complex behaviours including object use. For example, bowhead whales (Balaena mysticetus) are known to rub on rocks and some humpback whale (Megaptera novaeangliae) populations undertake lateral bottom feeding. Such underwater behaviour is difficult to observe but can play a critical role in the whales’ survival and well-being. Distinguishing social behaviours from those which serve a specific function remains challenging due to a lack of direct observations and detailed descriptions of such behaviours. A CATS (Customized Animal Tracking Solutions) suction cup tag with on board video and a 3D inertial measurement unit was deployed on three different humpback whales to assess their behaviour in the Gold Coast bay, Australia. Here, we present evidence of humpback whales (tagged and untagged individuals) performing bottom contact with prolonged rolling on sandy substrate. In addition, we showed that fish were actively feeding from the whales’ skin during this behaviour. We detail the behaviour and discuss possible drivers, with a focus on cetacean innovation, possible ectoparasite removal, and habitat preferences.